2018
DOI: 10.1021/acsomega.8b02212
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Properties of a 1D Helical Co(II) Coordination Polymer: Toward Single-Ion Magnetic Behavior and Efficient Dye Degradation

Abstract: This contribution deals with the synthesis and utilization of a new pyrazole-based unsymmetrical ligand, 3-(3-carboxyphenyl)-1 H -pyrazole-5-carboxylic acid (H 2 CPCA), for generating multifunctional materials. The reaction with the Co(II) salt in the presence of a co-ligand 2,9-dimethyl phenanthroline (dmphen) results in the formation of the helical compound {[Co 2 (dmphen) 2 (CPCA) 2 ]DMF} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…The h + , e – , and some common reactive species such as •OH, 1 O 2 , and •O 2 – are usually considered as active species that contribute to dye degradation. , Thus, different ROS scavengers, including isopropanol, KI, Cr­(VI), and TEMPOL, were added into the reaction system to identify the role of each reactive species. The results revealed that only the addition of Cr­(VI) resulted in a decrease in degradation (Figure f), suggesting that e – may be attributed to the degradation of MB.…”
Section: Resultsmentioning
confidence: 99%
“…The h + , e – , and some common reactive species such as •OH, 1 O 2 , and •O 2 – are usually considered as active species that contribute to dye degradation. , Thus, different ROS scavengers, including isopropanol, KI, Cr­(VI), and TEMPOL, were added into the reaction system to identify the role of each reactive species. The results revealed that only the addition of Cr­(VI) resulted in a decrease in degradation (Figure f), suggesting that e – may be attributed to the degradation of MB.…”
Section: Resultsmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have been continuously attracting much attention because of their appealing structural features as well as their potential applications in gas storage, guest molecule capture, dye degradation, sensing, heterogeneous catalysis, etc. The topology of MOFs is mainly dependent on the assembly of metals and organic ligands. The construction of MOFs starting from a simple ligand and metal ion do not always follow a preprogrammed design procedure. However, rational observations of reaction outcomes can give a hint to the reaction secrets that help to develop the desired product.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with 2D SIM frameworks, notably, only a small number of 1D Co( ii ) SIMs have been reported to date (Table S1†). 17,18…”
Section: Introductionmentioning
confidence: 99%